Analysis of lettuce transcriptome reveals the mechanism of different light/dark cycle in promoting the growth and quality - Dai, Mengdi; Tan, Xiangfeng; Ye, Ziran; Chen, Xuting; Zhang, Yi; Ruan, Yunjie; Ma, Bin; Kong, Dedong (Frontiers in Plant Science, 2024)
Light/dakr (L/D) cycle plays a crucial role in controlling the production and quality of vegetables.However, the mechanism of L/D cycle on vegetable growth and quality is scarce studied. To investigate the impact of L/D cycle on lettuce growth and quality, we designed three diel scenarios, including 16 hours of light and 8 hours of darkness (L16/D8), 12 hours of light and 6 hours of darkness (L12/D6), and 8 hours of light and 4 hours of darkness (L8/D4). Lettuce grew taller under the L8/D4 scenario than under L16/D8 light cycle scenarios. Under the L8/D4 scenario, the lettuce leaves exhibited greater enhancements in the levels of soluble protein, soluble sugar, and carotenoid content compared to the other scenarios. By comparing the expression levels under different diel scenarios (L16/D8 vs L12/D6, L16/D8 vs L8/D4, and L12/D6 vs L8/D4), we identified 7,209 differentially expressed genes (DEGs). Additionally, 3 gene modules that were closely related to L/D cycle of lettuce were selected by WGCNA analysis. The eigengenes of three gene modules were enriched in plant hormone signal transduction, sphingolipid metabolism, and nucleocytoplasmic transport pathways. Through network analysis, we identified six hub genes (CIP1, SCL34, ROPGEF1, ACD6, CcmB, and Rps4) in the three gene modules, which were dominant in plant circadian rhythms and greatly affected lettuce growth. qRT-PCR analysis confirmed the diurnal response patterns of the 6 hub genes in different treatments were significant. This study intensively enhanced our comprehension of the L/D cycle in the growth morphology, nutritional quality, and metabolic pathways of lettuce.